THE EFFECTIVENESS OF TELEVISION IN IMPROVING THE SCIENCE PROGRAM OF KINDERGARTEN TO GRADE 4 CLASSES IN NEW YORK CITY PUBLIC SHOOLS. - Reiner, William B. (Science Education, 1961)
The article focuses on the effectiveness of television in improving the science program in New York City public schools. A proposal was made that a series of television programs for classroom use in elementary science be included in the 1957-1958 schedules of television programs. The programs under the development by the television station WNYE and to be produced with the cooperation of the Metropolitan Educational Television Association over the station WP1X will be evaluated by the classroom teachers. The evaluation aims to determine the effect of the television presentation on the pupil's interests, awareness and involvement in science in their daily living. The result of the evaluation shows that the programs were effective in improving the science programs for kindergarten 2 to grade 4.